Hubungan Antara Cultural Values Dengan Organizational Citizenship Behaviour Pada Karyawan Etnis Tionghoa - Wiryateja, Jocelin; Michelle, Michelle; Cuangga, Evangelyn Grafany; Siahaan, Eirene Ratushyinkaya; Chandra, Angelina; Elvinawanty, Rianda (Jayapangus Press, 2024)
Organizational efficiency depends on high-quality human resources. Employee human resources difficulties often occur. However, there are some problems arising in relation to the human resources of employees where there are behaviors that indicate that there are activities that impede the performance of the organization and indicate the presence of some inappropriate staff. Corporate culture affects organizational citizenship behavior. The study examines and tests the relationship between cultural values and Organizational Citizenship Behavior (OCB) in ethnic Chinese workers. PT Capella Dynamic Nusantara involved 127 ethnic Chinese employees for research analysis using purposive sampling methods. This analysis uses quantitative data. This data is collected using surveys techniques through online media in particular Google Forms. This forms consists of 26 items of cultural value scale and 36 items of behavioral scale of organizational citizenship. The hypothesis put forward in this study is that there is a positive relationship between the cultural values of Chinese employees and the behavior of organizational citizenship. The calculation is done using an analytical test (hypothesis test) consisting of the Pearson Product Moment Correlation Test. The survey found a strong link between organizational citizenship behavior and cultural values. Employee cultural values and organizational citizenship behavior are positively correlated. Thus, cultural value rises with the existence of organizational nationality behaviors and vice versa. The correlation coefficient of 0.303 and p=0.05 is shown by data analysis, which suggests that there is a positive and significant relationship between cultural values and organizational citizenship behavior. In other words, the higher the cultural value, the greater the organizational citizenship behavior, and vice versa. From this study it can be concluded that the research hypothesis that states there is a positive relationship between cultural values and the behavior of citizenship of the organization is accepted.